PEER FEEDBACK IN FOREIGN LANGUAGE WRITING CLASS: STUDENTS’ PERCEPTION AND PROBLEMS - Agus Rofi'i (Journal of English Language Learning, 2020)
Many students claim that writing is the most difficult skills due to it is complicated in its production. In their learning, the students need a suitable method to help their writing. Peer feedback is the one of those methods that can support students’ learning writing in non-threatening atmosphere. This research aims to reveal EFL students’ problems in learning writingand students’ perceptions about peer feedback method in learning writing. In this research, the qualitative research design used was a case study through the instrument that are observation and interview for collecting the data. The participant of this research is eleventh grade of electricity engineering in one of vocational school in Majalengka. The result showed that students still faced the common problems in learning writing. The highest percentage of students’ problem is in vocabulary (45%) and the lowest percentage is in create content (5%). However, after implemented the practice of peer feedback, majority of the students provided the positive perceptions toward peer feedback. There is 70% students said that peer feedback helped them in learning writing. Also, they said that peer feedback has a number of benefits for their writing.